The Influence of Individual Caring and Organizational Trust on Organizational Commitment of Private LPTK Lecturers in Medan City - Khairtati Purnama Nasution; Zainuddin Zainuddin; Arif Rahman (BIRCU, 2020)
This study aims to reveal the influence of individual caring and organizational trust on organizational commitment of private LPTK lecturers in Medan city. This research design is classified as ex post facto research which has a causal relationship using a quantitative approThis research was conducted at private LPTKs throughout the city of Medan. This study was planned for 6 months. The population of this research is all lecturers who work in LPTK in Medan City. Based on data from each LPTK in Medan City, it was found that an overall population of 489 lecturersach. This research design uses a survey method. The data obtained from the measurement results were analyzed descriptively and inferentially. The stages in data analysis to be carried out in this study are descriptive analysis and inferential analysis. The results reveal that: 1. there is a significant effect of individual Carring variance on organizational trust. 2. there is a significant effect of Organizational Trust on Organizational Commitment.